PERANAN BMT AR-RAHMAH TERHADAP PENGEMBANGAN EKONOMI UMMAT DI KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Muhammad Abduh Anwar; Muhammad Aslam Ahmad; Zulkarnanin Sulaiman (JIA: Jurnal Ilmiah Administrasi, 2021)
In this research, there are two main problems, namely: the service pattern of BMT Ar-Rahmah Rappang as the quality of the community's economic improvement and the level of economic change concerning Rappang in the financing of BMT Ar-Rahmah to assess the point of satisfaction of its customers. This research describes the pattern or form of service implemented by BMT Ar-Rahmah Rappang with the quality of improvement and economic change in the ummah; its purpose is to assess the point of customer satisfaction. In data collection, used library research methods and field research using interview observation techniques and documentation. The collected data were processed using the descriptive and inductive methods. The results showed that BMT Ar-Rahmah Rappang is a sharia microeconomic financial business institution that is trusted by the public. In an effort to maintain and maintain its existence in such a tight competition, BMT always tries to carry out its service functions properly through professional service patterns and Islamic ethics, with various forms of services including the provision of facilities and infrastructure, innovative financial products, and employee performance. So that customers are always satisfied, and its existence as an institution for economic empowerment of the people, especially the middle to the lower class, so that it grows and develops.